1997
DOI: 10.1063/1.364259
|View full text |Cite
|
Sign up to set email alerts
|

Transport modeling of multiple-quantum-well optically addressed spatial light modulators

Abstract: Optically addressed spatial light modulators are essential elements in any optical processing system. Applications such as optical image correlation, short pulse auto-correlation, and gated holography require high speed, high resolution devices for use in compact, high throughput systems. Other important device criteria include ease of fabrication and operation. In this work we study the transport dynamics of a new kind of optically addressed spatial light modulator that uses semi-insulating or intrinsic quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 68 publications
(317 reference statements)
0
5
0
Order By: Relevance
“…The presence of a large density of trapping centers in the LTG material will inevitably produce a distribution of trapped charges within the MQW region, unlike STG MQWs where the trapped charges are concentrated at the MQW/cladding layer interfaces. 11 In this section, the space-charge field in the bright and dark regions is analyzed using a numerical simulation involving the standard continuity equations 12 for semiconductor materials in the presence of traps. It is shown that the space-charge field grows nonuniformly along the MQW growth direction.…”
Section: Numerical Simulation Of Space-charge Dynamics In the Ltgmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a large density of trapping centers in the LTG material will inevitably produce a distribution of trapped charges within the MQW region, unlike STG MQWs where the trapped charges are concentrated at the MQW/cladding layer interfaces. 11 In this section, the space-charge field in the bright and dark regions is analyzed using a numerical simulation involving the standard continuity equations 12 for semiconductor materials in the presence of traps. It is shown that the space-charge field grows nonuniformly along the MQW growth direction.…”
Section: Numerical Simulation Of Space-charge Dynamics In the Ltgmentioning
confidence: 99%
“…13 Asgrown samples with excess arsenic show evidence of a large density of point defects that coalesce into As precipitates with annealing. We use the standard photorefractive picture 11 to model the traps phenomenologically as deep, donor-like defects with a volume density N D that are partially compensated by shallow acceptors of density N A . The shallow traps are assumed for charge neutrality and play no role in the carrier dynamics.…”
Section: A Device Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Lateral drift within the MQW region was added heuristically. Figure 1 shows the division of the DPD in terms of SPD subdevices, each of which is split, as before, into an electro-optic region ͑containing MQWs where photocarriers are generated͒ sandwiched between two LTG layers, with an accumulation layer 14,15 at each MQW region/ LTG layer interface.…”
Section: Device Model For Distributed Structures: Extension Of Thmentioning
confidence: 99%
“…A number of publications were devoted to the analysis of transient grating formation in twodimensional ͑2D͒ geometry in the so-called perpendicular configuration ͑PERC͒ when the grating vector is normal to an externally applied electric field. [1][2][3][4] In these articles the emphasis was on the influence of field fringing and screening on the resolution of an optically addressed spatial light modulator based on a thin PR film. 2D studies of PR thin films were also done in the parallel configuration ͑PARC͒ when the external field is parallel to the grating vector, the configuration being useful for dynamic hologram enhancement.…”
Section: Introductionmentioning
confidence: 99%